OP0221 Radiographic progression of structural joint damage in patients with active psoriatic arthritis treated with ixekizumab over 52 weeks. (15th June 2017) - Heijde, D van der; Okada, M; Lee, C; Shuler, CL; Rathmann, S; Lin, C-Y; Mease, P
Abstract : Background: Ixekizumab (IXE), an anti-interleukin-17A monoclonal antibody, was shown to be superior to placebo (PBO) in clinical responses and inhibiting the progression of structural joint damage in patients (pts) with psoriatic arthritis (PsA) treated for 24 weeks (wks). 1 Objectives: To assess progression of structural joint damage in PsA pts with IXE for up to 52 wks. Methods: Biologic DMARD-naïve pts with active PsA (N=417) entered into SPIRIT-P1 (NCT01695239 ), a double-blind phase 3 trial. Pts must have had ≥1 joint erosion on the hand and foot x-rays confirmed by central reading or had a C-reactive protein level >6 mg/L at screening. 417 pts were randomized to IXE 80 mg every 2 wks (Q2W; N=103) or 4 wks (Q4W; N=107) following a 160 mg initial dose, PBO (N=106), or adalimumab 40 mg every 2 wks (ADA; active reference arm; N=101) for 24 wks. In the Extension Period (EXT: Wks 24–52), PBO and ADA pts were re-randomized (1:1) to IXEQ2W or IXEQ4W at Wk 16 (inadequate responders) or Wk 24; ADA pts underwent a washout prior to IXE treatment. All pts were assessed for structural joint damage using the van der Heijde modified PsA Total Sharp Score (mTSS, 0–528 scale). X-rays at Wks 0, 24 and 52 were scored independently by 2 readers blinded to timepoint and clinical data (average of readers). mTSS was excluded from the pre-specified analysis if the radiograph was taken after the scheduled visit date. In a post-hoc analysis, mTSS from a radiograph taken after the scheduled visit date was interpolated and considered as observed data. Any missing data at Wk 52, in either presentation, were imputed using a linear extrapolation if they had at least 1 post-baseline value. Results: Pts had active PsA at Week 0 (Table). 381 pts (91.3%) entered the EXT, with 374 (98.2%) having radiographs collected during the EXT. Wk 52 mean (SD) mTSS change from baseline were 0.54 (2.11) and 0.09 (1.0) for pts randomized to IXEQ4W and IXEQ2W at baseline, respectively. Similar changes at Wk 52 were obtained with the post-hoc analysis (Table). The majority of IXEQ2W or IXEQ4W pts exhibited no structural progression through 1 year of IXE treatment (Figure). In pts who switched from PBO or ADA to IXE, Wk 52 mean change from baseline mTSS values scores ranged from -0.03 to 0.41 (Table). Conclusions: Over a 52 wk period, minimal changes in mTSS were observed in PsA pts entering the EXT and treated with IXEQ2W or IXEQ4W. References: Mease P et al. 2017 ARD 76(1):79. Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boeringer Ingelheim, Celgene, Daiichi, Eli Lilly and Company, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, UCB, M. Okada Grant/research support from: Eli Lilly and Company, Consultant for: Eli Lilly and Company, Speakers bureau: Santen Pharmaceutical, Mitsubishi Tanabe Pharma, Pfizer, Abbott Japan, C. Lee Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Shuler Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Rathmann Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C.-Y. Lin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Mease Grant/research support from: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Eli Lilly and Company, Merck, Novartis, Pfizer, UCB Pharma, Sun, Consultant for: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Eli Lilly and Company, Merck, Novartis, Pfizer, UCB Pharma, Sun, Speakers bureau: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Pfizer, UCB Pharma